ADVANCE PASSENGER INFORMATION SYSTEM INTEGRATION IN IMMIGRATION CLEARANCE FOR NON-REGULER SHIP - Gunawan Ari Nursanto (Jurnal Ilmiah Kajian Keimigrasian, 2018)
Integration of APIS into the Immigration’s information and technology system is very important and urgent to be carried out in order to assist the implementation of the Indonesian Immigration function and functions carried out by the Directorate General of Immigration to mitigate the risks arising from legal migration carried out between countries, whether in regional and global migration. APIS itself is a data communication system developed by the Government of the United States of America which contains data on passengers from operators of a commercial or private transport cororation from the country of origin, sent via electronic transmission to operators in the destination country which aims to initial identification of passengers. Article 6 of 2011 concerning Immigration has mandated the responsible transportation corporation to carry out the Integration of the APIS system is very important in relation to the implementation of the immigration function, especially in supervision. Indonesia, which is a maritime state, should implement and integrate the APIS system in the Immigration Cleaance of Non Reguler Ships in immediate fashion, currently this is still conducted semi-electronical via e-mail, this condition could provide a gap that can cause vulnerability in the implementation of the Migration Clearance, especially in the aspect of Supervision in Imigration Clearance for Non Reguler Ships.